Digital Religion Tourism : Pengembangan Desa Wisata Religi Nyai Ageng Ngerang Berbasis Digital - Khoiriyah, Nur (Institut Agama Islam Negeri (IAIN) Kudus, 2025)
Digital Religious Tourism: Digital-Based Development of the Nyai Ageng Ngerang Religious Tourism Village. This Community Service Program aims to develop religious tourism villages digitally. The initial discovery process revealed a strong socio-religious asset, the Tomb of Nyai Ageng Ngerang. This Community Service Program (PKM) utilized the ABCD method, which provides opportunities for community development based on existing potential. The result of the Community Service Program was a discussion on the development of religious tourism at the Tomb of Nyai Ageng Ngerang. This event was dynamic and lively. Participants enthusiastically presented various questions and proposed developments based on the material presented by the speakers.